TECHNOLOGY INTEGRATION USING OUTCOME BASED EDUCATION APPROACH IN TEACHING INTRODUCTORY PHYSICS - Navarro, Leah (PEOPLE: International Journal of Social Sciences, 2017)
The study was focused on determining the effectiveness of an approach in education which is outcome-based and integrated technology in teaching introductory physics among second year BSIT/BSCS students of Cavite State University enrolled in six (6) chosen campuses during the second semester of school year 2014-2015. Through Purposive sampling and census method three hundred fifty nine (359) students and eight (8) instructors were used as participants respectively. The researcher used Quasi-experimental research design. Seven (7) instruments were employed in the study. At p<0.05 level of significance using t-test independent mean, standard deviation, percentage and Analysis of Co-Variance(ANCOVA) hypotheses were tested. The result suggests that the technology integration intervention used for physics instruction utilized by the experimental group was effective in improving the students’ test scores. Results revealed the rejection of three null hypotheses tested thus, development of learning plans employing Technology Integrated Strategy (TIS) using outcome based education approach is highly recommended to actively involve the students in the teaching- learning process. The study conducted was limited in determining the effectiveness of TIS in teaching physics, therefore it is recommended to replicate the study in other discipline and the instrument crafted by the researcher may be used by other institution in promoting technology integrated lesson presentations. Administrators are highly encouraged to initiate the conduct of workshop about the use of TIS on various disciplines through continuing education program.